Chemical Composition, Antifungal and Anti-Biofilm Activities of Volatile Fractions of Convolvulus althaeoides L. Roots from Tunisia - Soukaina Hrichi; Raja Chaâbane-Banaoues; Filippo Alibrando; Ammar B. Altemimi; Oussama Babba; Yassine Oulad El Majdoub; Habib Nasri; Luigi Mondello; Hamouda Babba; Zine Mighri; Francesco Cacciola (Molecules, 2022)
The antifungal drugs currently available and mostly used for the treatment of candidiasis exhibit the phenomena of toxicity and increasing resistance. In this context, plant materials might represent promising sources of antifungal agents. The aim of this study is to evaluate for the first time the chemical content of the volatile fractions (VFs) along with the antifungal and anti-biofilm of Convolvulus althaeoides L. roots. The chemical composition was determined by gas chromatography coupled to a flame ionization detector and mass spectrometry. In total, 73 and 86 chemical compounds were detected in the n-hexane (VF1) and chloroform (VF2) fractions, respectively. Analysis revealed the presence of four main compounds: n-hexadecenoic acid (29.77%), 4-vinyl guaiacol (12.2%), bis(2-ethylhexyl)-adipate (9.69%) and eicosane (3.98%) in the VF extracted by hexane (VF1). n-hexadecenoic acid (34.04%), benzyl alcohol (7.86%) and linoleic acid (7.30%) were the main compounds found in the VF extracted with chloroform (VF2). The antifungal minimum inhibitory concentrations (MICs) of the obtained fractions against Candida albicans, Candida glabrata and Candida tropicalis were determined by the micro-dilution technique and values against Candida spp. ranged from 0.87 to 3.5 mg/mL. The biofilm inhibitory concentrations (IBF) and sustained inhibition (BSI) assays on C. albicans, C. glabrata and C. tropicalis were also investigated. The VFs inhibited biofilm formation up to 0.87 mg/mL for C. albicans, up to 1.75 mg/mL against C. glabrata and up to 0.87 mg/mL against C. tropicalis. The obtained results highlighted the synergistic mechanism of the detected molecules in the prevention of candidosic biofilm formation.